LANGUAGE BARRIER IS THE CAUSE OF STRESS AMONG INTERNATIONAL STUDENTS OF UNIVERSITAS AIRLANGGA - Shahzad Ali; Nono Hery Yoenanto; Duta Nurdibyanandaru (Universitas Sebelas Maret, 2020)
Advanced education system and globalization are attractive towards the students to move a foreign country for achieving higher education. Indonesia is a multicultural and multi-linguistic country where every year hundreds of students coming to get higher education in Masters and PhD in various disciplines of education which are taught in Indonesian language. There are number of students joining Universitas Airlangga for the purpose of higher education on different programs. The current investigation defines the problem of language barrier is causing of stress in regard of academics among international students. There were 70 international students contributed in current study. The study finds 68% of participants suffering with the stress of language barrier in academics for international students. The findings of current study indicated the mainstream of international students experiencing in adopting the language barrier which is becoming the cause of stress for them. This study also suggested to the administrative stack-holders of Universitas Airlangga to pay attention this issue and need to overcome this major problem by organizing some events within the campus with local students. Such recommendations will help to cope this issue among international students by learning in a lenient and practical way.